2015
DOI: 10.1186/s13104-015-1064-5
|View full text |Cite
|
Sign up to set email alerts
|

Understanding action on the social determinants of health: a critical realist analysis of in-depth interviews with staff of nine Ontario public health units

Abstract: BackgroundAddressing the social determinants of health (SDH) is identified as a role for local public health units (PHUs) in the province of Ontario. Despite this authorization to do so there is wide variation in PHU practice. In this article we consider the factors that shape local PHU action on the SDH through a critical realist analysis.MethodsInterviews with Medical Officers of Health (MOHs) and lead staff from nine PHUs in Ontario identify the structures and powers that allow PHUs to address the SDH as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(28 citation statements)
references
References 11 publications
1
25
0
2
Order By: Relevance
“…In our report [ 9 ], we found that health equity was conceptualized in various ways, along a spectrum from a burden of disease approach on one end to a health equity approach on the other end. In addition, it has been shown that PHUs were working toward health equity in very different ways, from direct service provision to enhancement of socioeconomic conditions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In our report [ 9 ], we found that health equity was conceptualized in various ways, along a spectrum from a burden of disease approach on one end to a health equity approach on the other end. In addition, it has been shown that PHUs were working toward health equity in very different ways, from direct service provision to enhancement of socioeconomic conditions [ 11 ].…”
Section: Resultsmentioning
confidence: 99%
“…One of the reasons writing an overarching OPHS and PPM may have been difficult is because of the wide range of ways in which health equity has been operationalized in the province. Raphael and Brassolotto [ 11 ] discussed three differing approaches to addressing SDOH, 1) service delivery, 2) intersectoral and community, and 3) structural [ 11 ]. Pinto et al [ 3 ] identified that the recognition of “how equity is conceptualized” would assist in developing “more explicit, action-oriented and concrete steps” to address health equity (p.8).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11,12]That complements the health care provided by a physician and may potentially result convenience for patients to get their refills in minimum time spent dealing with prescription changes and combined medication management. [14,16] The role of the pharmacist has changed a lot over the last twenty year. A widely expansion in scope of practice has gone far beyond a traditional dispensing.…”
Section: Pharmaceutical Portfolio In Canadamentioning
confidence: 99%
“…Academics, for example, navigate review and funding structures that systematically privilege particular groups [14,15] and ideologies [16,17]. In public health practice, efforts to respond to social determinants of health have a tendency to become narrowly focused on behavioural interventions [18][19][20]. In policy settings, advancing policies to redress imbalances in the distribution of wealth, resources, and power lack traction [21][22][23].…”
Section: Introductionmentioning
confidence: 99%